The flank wear optimisation of 316 Stainless Steel using response surface method in dry-down milling using carbide insert - Nurul Hidayah, Razak; N. F., Husein (Institution of Engineering and Technology, 2022)
316 stainless steel is widely known as difficult to machine material and as a result of the excellent mechanical properties that it possesses, the tendency of tool breakage is very high. Thus, it becomes a major concern in machining field industry. Therefore, the study on the optimisation of the cutting parameters during machining 316 stainless steel is crucial. This study has been conducted on 316 stainless steel in dry down-milling with the use of carbide inserts. In identifying the dominant cutting parameters that affect flank wear and the optimum cutting parameters to optimise the flank wear, response surface (RSM) method was used. From the observation, it was found that the factor that was most influential was the feed rate, and subsequently followed by cutting speed and depth of cut. The combination of 0.2 mm/tooth feed rate, 100m/min cutting speed, and of 0.8mm depth of cut made optimum milling parameters.